SiC-Based nanocomposites for coating applications involving wear and corrosion resistance - Druzian, Daniel Moro; Oviedo, Vinícius Rodrigues; Fernandes, Liana da Silva; Rodhen, Cristiano Rodrigo Bohn; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Nanocomposites containing SiC as the nano-reinforcement have been widely used in various fields, such as aerospace, automotive, military, and marine industries. In materials engineering, wear and corrosion are two common problems for several applications. Thus, the effects of adding SiC nanoparticles to composites have been studied to improve their physical-chemical and mechanical properties, such as corrosion and wear resistance. In this context, this paper aims to overview the current investigations on nanocomposites containing SiC nanoparticles as the reinforcement, and with focus on application as a coating involving wear and corrosion resistance. The research was carried out in the ScienceDirect and Web of Science databases, where the papers were selected using the descriptors ‘ceramic reinforcement’, ‘nanocomposite’, ‘coating’, ‘SiC’, ‘silicon carbide’, ‘wear resistance’, ‘corrosion resistance’ and ‘applications’. From this review, 17 scientific articles were found from 1998 to August-2021 involving the application in wear and corrosion resistance. The studies showed improvement on corrosion and wear resistance with the use of SiC-based nanocomposite coatings. Therefore, the differences in the presented results were due to the size and quantity of SiC nanoparticles used in the nanocomposites, being then, able to be used for material applications involving resistance to wear and corrosion.